ANTIMICROBIAL ACTIVITY OF BURSERA MORELENSIS RAMÍREZ ESSENTIAL OIL - Canales-Martinez, M.; Rivera-Yañez, C.R; Salas-Oropeza, J.; Lopez, H.R; Jimenez-Estrada, M.; Rosas-Lopez, R.; Duran, D.A.; Flores, C; Hernandez, L.B; Rodriguez-Monroy, M.A (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Bursera morelensis, known as “Aceitillo”, is an endemic tree of Mexico. Infusions made from the bark of this species have been used for the treatment of skin infections and for their wound healing properties. In this work, we present the results of a phytochemical and antimicrobial investigation of the essential oil of B. morelensis.Materials and Methods: The essential oil was obtained by a steam distillation method and analyzed using GC-MS. The antibacterial and antifungal activities were evaluated. Results: GC-MS of the essential oil demonstrated the presence of 28 compounds. The principal compound of the essential oil was α-Phellandrene (32.69%). The essential oil had antibacterial activity against Gram positive and negative strains. The most sensitive strains were S. pneumoniae, V. cholerae (cc) and E. coli (MIC 0.125 mg/mL, MBC 0.25 mg/mL). The essential oil was bactericidal for V. cholera (cc). The essential oil inhibited all the filamentous fungi. F. monilifome (IC50 = 2.27 mg/mL) was the most sensitive fungal strain. Conclusions: This work provides evidence that confirms the antimicrobial activity of the B. morelensis essential oil and this is a scientific support about of traditional uses of this species.